Neutropenia in Cynomolgus Monkeys With Anti-Drug Antibodies Associated With Administration of Afucosylated Humanized Monoclonal Antibodies. (December 2022) - Adedeji, Adeyemi O.; Zhong, Fiona; Getz, Jennifer A.; Zhong, Zoe; Halpern, Wendy
Removal of the core fucose from the Fc region of humanized monoclonal antibodies (afucosylated antibodies) enhances their antibody-dependent cell cytotoxicity activities in killing cancer cells. Based on the authors' experience and literature, administrations of afucosylated antibodies have been associated with neutropenia in cynomolgus monkeys. However, in a recent general toxicology study conducted with an afucosylated antibody in cynomolgus monkeys, transient neutropenia was observed and correlated with the emergence of anti-drug antibodies (ADAs) in the affected animals. To further explore the relationship between neutropenia, afucosylated antibodies, and ADAs in cynomolgus monkeys, we performed an investigational retrospective meta-analysis of data from general toxicology studies conducted with Genentech's therapeutic antibodies administered to cynomolgus monkeys between 2005 and 2021. In this analysis, transient neutropenia strongly correlated with ADA-induced inflammation in cynomolgus monkeys administered afucosylated antibodies. This may reflect the simultaneous occurrence of two distinct processes of neutrophil elimination and utilization, thus overwhelming bone marrow reserve capacity leading to transient neutropenia. The integrated analysis of immunogenicity, and anatomic and clinical pathology results from these studies highlights the correlation of transient neutropenia in cynomolgus monkeys with ADA-related inflammation, potentially exacerbated by enhanced effector function of afucosylated antibodies.